Depositors’ perception on performance in Nepalese commercial banks - Lamichhane, Pitambar (Management Dynamics, 2020)
This paper analyzes bank depositors’ perception in relation to factors explaining performance of banks in Nepal. This study has applied descriptive and explorative research design to analyze factors affecting bank performance. A survey was made to collect data from bank depositors using structural questionnaire in Kathmandu valley in 2019. Survey result reveals that Nepalese depositors prefer to deposit money in commercial banks because of easy access but are not satisfied with e-banking services. Most of depositors have no ownership in banks and feel interest rate on deposits is less than expectations. Similarly, result shows that depositors prefer to deposit in saving account analyzing risk and feel government rules and regulations affect interest rates of banks. Further, result indicates banks’ image and interest rate on deposits are key factors for bank deposits and performance, poor operating performance and lack of appropriate investment opportunities are reasons of low interest rate on bank savings. Finally, result concludes that use of modern technologies, size of deposits, market information, managerial efficiency, size of lending and deposits of banks are significant factors and size of debt capital and assets are weak factors affecting performance in Nepalese commercial banks.